Pemberdayaan Pelaku UMKM dalam Meningkatkan Kapasitas Berwirausaha Secara Berkelanjutan Melalui Program Bestee di BTPN Syariah di Medan - Romindo Pasaribu; Juara Simanjuntak; Vinsensius Matondang; Bilson Pandiangan (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2025)
PT Bank BTPN Syariah is one of the banks with a mission to provide access, education, and guidance to MSMEs spread across Indonesia. PT Bank BTPN Syariah invites students from public and private universities to join the Bestee program. Currently, PT Bank BTPN Syariah has empowered 37,311 MSMEs in 682 sub-districts spread across Indonesia. The entrepreneurial mentoring conducted by students as facilitators is part of PT Bank BTPN Syariah's mission. In the Bestee program, students act as facilitators, providing mentoring activities to SME entrepreneurs to expand market access both online and offline. The mentoring and empowerment activities for SME operators were conducted at the homes of PT Bank BTPN Syariah customers in Medan, specifically in the sub-districts of Medan Johor, Medan Labuhan, and Medan Timur, from March to May 2025. The first stage involved customer assessment. The second stage involved delivering instructional materials during the second week of mentoring. The third phase involves reviewing and practicing the material taught in the previous meeting. The fourth and final phase is the closing session, where the facilitator assists customers in enhancing their knowledge to maximize business development, leverage marketing technology, and provide crucial information on business identity, promotion, business diversification, excellent service, licensing, financial record-keeping, and appropriate partner materials.